PERAN PENGHULU DALAM UPAYA MEMINIMALISIR TINGKAT PERCERAIAN - Sahlan Habibi Siregar (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2022)
The abstract This study aims to determine the role of the penghulu in minimizing the divorce rate. The research method used in this study is a literature study method which is included in the type of qualitative descriptive. By descriptive, knowing the description of the efforts that can be done by the penghulu to minimize the divorce rate, then with a literature study that shows the results of previous studies that support the ideas generated in this study. The results of this study conclude that there are several efforts that can be made by the penghulu in an effort to reduce the divorce rate in society, including: 1). Implementation of premarital guidance, 2). Forming a sakinah family study group, 3). do special guidance, 4). Reactivating the Advisory Board for the Development and Preservation of Marriage (BP4), 5). Meghan Wedding to be held at a young age, 6). Bride and Groom Guidance, and 7). Optimizing Intersectoral Coordination.